過疎問題の人口論的考察 - 皆川 勇一 (人口学研究, 1989)
Ever since 1960, most of the remote mountain villages in Japan has experienced heavy out-flow of native junior and senior high school graduates, and young farmers. Furthermore, growing number of farm families has moved to city regions. Population and households of the remote villages diminished severely. As a result, many difficulties arose both in industrial activities and in daily life of the region. We call it "KASO problem" in the gross. The "KASO region" contains all the communities suffering from this "KASO problem". From about 1965, the national and local government authorities grasped the severeness of "KASO problem". They have planned and introduced many counter-measures to mitigate and conquer those problems. After twenty years of efforts, has "KASO problem" improved much better? How is the present status of KASO regions? I examined in this paper these two subjects chiefly from demographic viewpoint. According to the White Paper on KASO (that is the yearly governmental publication explaining the status of KASO regions and governmental counter-measures), total population of KASO regions decreased from 12,75 million of 1960 to 8.17 million of 1985. But now the heavy out migration in the 1960's has almost calmed. The intercensal population decrease was more than 10% in the 1960's, But, in the 1980-85 period it fell off to 3%. The number of local communities that experienced population diminution of 10% and above decreased from 877 in the 1965-70 period to 107 in the 1980-85. However, the population decrease of KASO regions has never stopped. The heavy out-flow of youngsters continues even now. As the resultant severe aging of population, the rise of death rate will become remarkable. The result of population projection shows that the rate of population decrease will rise to the double in the 2005 year. At present, the most serious social problem in KASO regions is a rapid increase in the number and the proportion of population aged 65 and above. The proportion reached 17% in 1985 (as for national population, it is 10.3%), and the speed of aging process will become much faster. In 2005 the proportion will augment to 27.5%. Accompanied with aging, natural decrease of population will grow even larger, and the number of old aged couples and elderlies living alone will increase rapidly. The aging aggravates the social welfare, but the more serious problem is its negative effects on the growth of local economy. In the 1970's, local economy has showed a marked development. The first basis of the growth was the abundance of native upper midde and old age population. Most of them were owner farmers. They worked on their own farm, and most of them had a side job. Their industriousness has worked as a driving force of the enlargement of local economy in the 1970's. But, most of them will be compelled to retire altogether from their jobs in the near future. Therefore, the source of supply of cheap and efficient labor in the local economy will dry up. Such a cursed process will cause maximal damage to the economy of KASO regions. The revitallization of local industry and community life in KASO regions now is the most difficult problem to the regional policy of Japan. 1960年頃から,農山村および山村地域では,新規学卒者ならびに若者の激しい都市への流出,中高年層にまでおよぶ出稼ぎ,さらに,大量の挙家離村が生じ,その結果,地域人口および世帯の減少が顕著となった。これらの現象およびそれにともなう産業衰退ならびに農山村住民の生活困難が過疎問題である。この過疎の問題が認識され,過疎への対応策が取られてから20年を経た今日,過疎地域はどのような状況にあるか,過疎問題は改善されたと言えるだろうか。本稿ではこうした問題を人口学的側面から検討した。過疎白書にもとづき過疎地域の人口の動向をみると, 1960年代の急激な人口流出とくらべ,最近では,全体としての人口減少は鎮静化しつつある。1960年代のセンサス間人口減少率は10%をこえていたが, 1980〜85年間には3%台に低下し,各センサス間に10%以上の人口減少をみた市町村数も, 1965〜70年期の877から, 1980〜85年期には107に減少した。しかしながら,若年層の人口流出率は依然高い。その上,過去20年以上にわたる若年層の流出の必然的結果である人口老齢化にもとづく出生減と死亡率の上昇によって,過疎地域の人口減少率は今後ふたたび上昇することが将来推計によって明らかにされている。現在,過疎地域の最も深刻な問題は高齢者比率の急上昇である。過疎地域全体の65歳以上の人口の比率は, 1985年現在, 17%に達しており,今後の老齢化の進行も全国にくらべはるかに急速と推計される。この結果,過疎地域では,これから人口の自然減がさらに増大し,高齢者夫婦および高齢者の一人暮らしの世帯が急激に増加することになる。高齢化の進行は過疎地域の社会福祉問題を深刻化させるが,さらに今ひとつの問題は,'高齢化が地域経済の動向におよぼす影響の大きさである。1970年代には,地方経済のささやかな成長が生じたが,それを可能にした第一の主体的条件は,地元居住の中高年世代の多就業化であった。20代30代の若者の大量流出にもかかわらず,戦後農村部に留まりつづけた現在50歳以上層の多就業化こそが70年代の地方経済の拡大の一つの基礎条件であった。しかし,今後これらの就業者は引退ないし死亡し,地方の労働力の供給源は急速に萎縮せざるをえなくなる。とくに過疎地域ではこれは深刻な問題である。村おこし町づくりが様々な形で試みられるなかで,過疎地域の産業ならびに生活の再構成は,当面の地域政策に対し最大の難問を提起している。